National and sub-national HIV/AIDS epidemiology, socioeconomic influences, and risk factors in Iran from 1990 to 2021, global burden of disease 2021 study - Seyed Aria Nejadghaderi; Mohammad-Mahdi Bastan; Mohammadamin Abdi; Abedin Iranpour; Hamid Sharifi (Scientific Reports)
Abstract Human immunodeficiency virus (HIV) remains a global health challenge. Iran faces significant HIV issues with rising incidence and mortality rates. While antiretroviral therapy has improved life expectancy, projections indicate an above-average increase in the next years. We aimed to report the national and subnational burden of HIV/AIDS and risk factors in Iran from 1990 to 2021 by sex, age, and socio-demographic index (SDI). The analysis used the Global Burden of Disease 2021 data on age-standardized incidence rates, prevalence, death, and disability-adjusted life years (DALYs). The Cause of Death Ensemble Model was used to estimate HIV mortality and DisMod-MR 2.1 for non-fatal outcomes. Comparative risk assessment was conducted to evaluate the burden of HIV/AIDS attributable to risk factors such as condomless sex, drug use, and intimate partner violence. A smoothing splines model was used to determine the relationship between SDI and age-standardized DALY rates for HIV/AIDS. The counts and rates were reported with 95% uncertainty intervals. In 1990, the age-standardized incidence rate of HIV/AIDS in Iran among both sexes was 0.2 (0.1, 0.7), the prevalence rate was 1.5 (1.0, 2.5), the death rate was 0.1 (0.1, 0.1), and the DALY rate was 4.2 (4.1, 4.4) per 100,000. In 2021, age-standardized proportions per 100,000 were as follows: incidence 2.3 (1.8, 3.0), prevalence 21.6 (17.6, 26.4), death 0.6 (0.6, 0.6), and DALY 31.7 (30.8, 32.9). Males had higher age-standardized rates than females in 2021. However, females showed a higher relative increase in age-standardized rates from 1990 to 2021. In 2021, the 35–39 age group observed the highest DALY rates. Drug use was the leading risk factor 19.9 (18.7, 21.1), followed by condomless sex at 5.1 (4.5, 5.8). The age-standardized DALY rate increased with SDI up to the SDI of 0.65, after which it decreased. The most affected provinces were Kermanshah, Hormozgan, and Fars. The burden of HIV in Iran has risen significantly, with males and young adults most affected. Drug use was the leading risk factor for the infection. In the following years, interdisciplinary education, policy, and healthcare efforts are necessary to reduce the burden and incidence.